2019
DOI: 10.1111/pbi.13106
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9‐mediated knockout of Ms1 enables the rapid generation of male‐sterile hexaploid wheat lines for use in hybrid seed production

Abstract: Summary The development and adoption of hybrid seed technology have led to dramatic increases in agricultural productivity. However, it has been a challenge to develop a commercially viable platform for the production of hybrid wheat (Triticum aestivum) seed due to wheat's strong inbreeding habit. Recently, a novel platform for commercial hybrid seed production was described. This hybridization platform utilizes nuclear male sterility to force outcrossing and has been applied to maize and rice. With the recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(79 citation statements)
references
References 38 publications
2
76
0
1
Order By: Relevance
“…In wheat, CRISPR‐Cas9 gene editing was successfully applied to modify such traits of agronomic value as disease resistance (Wang et al ., ), gluten content (Sánchez‐León et al ., ), protein content (Zhang et al ., ), male sterility (Okada et al ., ) and grain size and weight (Wang et al ., ; Zhang et al ., , ). These studies also demonstrated that the editing of either individual copies of duplicated genes on homoeologous chromosomes or all three homoeologous copies of genes is possible (Wang et al ., 2014, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…In wheat, CRISPR‐Cas9 gene editing was successfully applied to modify such traits of agronomic value as disease resistance (Wang et al ., ), gluten content (Sánchez‐León et al ., ), protein content (Zhang et al ., ), male sterility (Okada et al ., ) and grain size and weight (Wang et al ., ; Zhang et al ., , ). These studies also demonstrated that the editing of either individual copies of duplicated genes on homoeologous chromosomes or all three homoeologous copies of genes is possible (Wang et al ., 2014, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in barley reported CRISPR/Cas9-induced mutation frequencies of 10-23% (Lawrenson et al, 2015), 44% (Holme et al, 2017) and ~80% (Gasparis et al, 2018;Kapusi et al, 2017) of plants after Agrobacterium-mediated transformation. In other cereals such as wheat, mutant production efficiency was reported from 0.3-5% using biolistic bombardment of CRISPR/Cas9 components (Zhang et al, 2016;Gil-Humanes et al, 2017;Liang et al, 2017;Sánchez-León et al, 2018) and Agrobacterium-mediated transformation (Okada et al, 2019). In the T0 plants described here, all mutants were heterozygous (monoallelic) across the targeted genes, with 83% of the lines carrying short InDels 3-4 bp upstream the PAM sequence.…”
Section: Discussionmentioning
confidence: 88%
“…Agrobacterium-meditated transformation is a straightforward approach to plant transformation resulting in the insertion of only one or a few copies of the transgene (Kohli et al, 2003;Travella et al, 2005). Several reports describe the use of Agrobacterium-delivered CRISPR/Cas9 for wheat genome editing, despite the low transformation efficiency of this crop (Zhang et al, 2018a(Zhang et al, , 2019Howells et al, 2018;Okada et al, 2019).…”
Section: Introductionmentioning
confidence: 99%